Pengaruh Etos Kerja Islam terhadap Kepuasan Mahasiswa di Layanan Akademik Fakultas Dakwah UIN KHAS Jember - Sundosia, Iin; Rahman, Muthi’ah; Rahayu, Eko; Fitriana, Aniqotuzzuhro' (Medan Resource Center, 2023)
Work ethic is the attitude of a person or group that influences attitudes at work, referring to divine values as the basis for living life. Meanwhile, the Islamic work ethic is the perspective believed by a Muslim in completing his work, according to the commands of Allah SWT. that work as a manifestation of good deeds and forms of worship. In the academic service of the Da'wah Faculty of UIN Khas Jember, the majority of its employees are Muslims. Therefore, the values of the work ethic should be a guideline in serving the needs of da'wah faculty students in the academic field. The Islamic work ethic is reflected in 15 characteristics including honesty, discipline, responsibility, istiqomah, shyness, thrifty and efficiency, creative, leadership spirit, actively seeks knowledge, friendship, consequences and dares to face challenges, sincere, tenacious, self-respect and Trust. This study used a descriptive quantitative method with the independent variable namely Islamic work ethic (x) and the dependent variable namely student (customer) satisfaction (y). The influence of the application of the Islamic work ethic in the Da'wah Faculty of UIN Khas Jember on student satisfaction is 38.3%.